2021
DOI: 10.3389/fpls.2021.709453
|View full text |Cite
|
Sign up to set email alerts
|

Differential Nutrient Uptake by Saltmarsh Plants Is Modified by Increasing Salinity

Abstract: In Southern European estuaries and associated salt marshes, the anthropogenic nutrient inputs, together with longer drought periods, are leading to increasing eutrophication and salinization of these coastal ecosystems. In this study, uptake kinetics of ammonium, nitrate, and phosphate by three common plants in Palmones salt marsh (Southern Spain), Sarcocornia perennis ssp. alpini, Atriplex portulacoides, and Arthrocnemum macrostachyum were measured in hydroponic cultures. We also determined how these uptakes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…At the same time, increased flushing, and therefore more oxidized conditions, could promote plant growth and in turn increase organic matter supply to the sediments, which could result in increased NH 4 accumulation as it decomposes. Finally, nutrient uptake by salt marsh vegetation varies by species and is influenced by interspecific competition and salinity, so variability in resident plant communities as well as porewater salinity may explain differences in concentrations of NH 4 and PO 4 [ 22 , 55 , 56 ]. In spite of the potential variability resulting from the interplay between sedimentary conditions, hydrology, and vegetation growth, we observed a clear overall trend of increasing nutrient concentrations across the marsh platform over time.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, increased flushing, and therefore more oxidized conditions, could promote plant growth and in turn increase organic matter supply to the sediments, which could result in increased NH 4 accumulation as it decomposes. Finally, nutrient uptake by salt marsh vegetation varies by species and is influenced by interspecific competition and salinity, so variability in resident plant communities as well as porewater salinity may explain differences in concentrations of NH 4 and PO 4 [ 22 , 55 , 56 ]. In spite of the potential variability resulting from the interplay between sedimentary conditions, hydrology, and vegetation growth, we observed a clear overall trend of increasing nutrient concentrations across the marsh platform over time.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been suggested that—for S. ambigua cultivated in a biofloc‐based aquaponics system under salinities ranging from 8‰ to 32‰—ammonium uptake is favoured under brackish water salinities (16‰), due to higher nitrate and lower ammonium water concentrations being observed in that treatment (Pinheiro et al, 2020). Another study evaluating the differential nutrient uptake of different salt marsh halophytes, including one species of the Sarcocornia genus, found out that the uptake rates of both ammonium and nitrate were negatively affected by an increase in salinity (Carmona et al, 2021). Still, previous publications evaluating the aquaponics production of S. ambigua under salinities similar to the one found in this study achieved higher plant productivities than presently reported—for example, Pinheiro et al (2017) observed salinities ranging from 31‰ to 38‰ in the aquaponic production of S. ambigua and found a productivity of 8.2 ± 0.3 kg m −2 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study evaluating the differential nutrient uptake of different salt marsh halophytes, including one species of the Sarcocornia genus, found out that the uptake rates of both ammonium and nitrate were negatively affected by an increase in salinity (Carmona et al, 2021). Still, previous publications evaluating the aquaponics production of S. ambigua under salinities similar to the one found in this study achieved higher plant productivities than presently The increase in nitrate concentration observed throughout the experiment can be attributed to the fact that the biofloc management strategy adopted in this study was to favour a chemoautotrophic system, a system in which nitrification is the metabolic pathway favoured for ammonia removal (Ebeling et al, 2006), first through the use of mature biofloc water-that is, water from a biofloc tank in which the nitrifying community is already established (Emerenciano et al, 2017;Krummenauer et al, 2014)-and second by the use of organic carbon supplementation only in situations with instability in the concentrations of the nitrogenous compounds, as adopted in other publications (Ferreira et al, 2021;Martins et al, 2020).…”
mentioning
confidence: 99%
“…Another important environmental factor we have not so far considered is the level of nutrients, which is also related to climate changes and anthropogenic pressures on salt marshes (Ratliff et al, 2015;Newton et al, 2020;Hughes et al, 2021). Since salt marshes are nitrogen-poor, yet very productive environments, they are potentially much sensitive to changes in nutrient availability (Valiela and Teal, 1974;Pennings et al, 2002;Muench and Elsey-Quirk, 2019;Carmona et al, 2021;Giblin et al, 2021) In fact, eutrophication may have marked effects on marsh plant community structure by shifting the competitive balance among plants and consequently altering the zonation and species composition of plant communities (Levine et al, 1998). Field experiments demonstrated that there exists a nutrient-dependent competitive hierarchy, with competitive outcomes being typically reversed when nutrients were abundant as better stress tolerators become dominant competitors (Emery et al, 2001).…”
Section: Model Limitations and Future Developmentsmentioning
confidence: 99%